Penegakan Hukum Terhadap Pelanggaran Hak Asasi Manusia Ditinjau Dari Hukum Internasional - Sahad, Indri Yulia; Tuhulele, Popi; Riry, Welly Angela (PATTIMURA Law Study Review, 2024)
ABSTRACT: Based on the Universal Declaration of Human Rights (UDHR) in article 18 which states "everyone has the right to freedom of thought, heart, conscience, religion, in this case it means the freedom to change religion or belief, by teaching it, practicing it, worshiping or obeying it, whether alone or together with other people, in public or alone.” China Sentences Uyghur Woman to 14 Years in Prison for Teaching Islam The Chinese government reportedly arrested and sentenced a Uyghur Muslim named Hasiyet Ehmet to 14 years in prison just for teaching Islam and keeping a copy of the Koran. The discussion that will be studied in this writing is to find out and analyze the forms of violations of Uighur Muslims by the Chinese government and to know and analyze the enforcement of International Human Rights law against the Chinese government, even though it has not ratified the 1998 Rome Statute. In accordance with the problems raised, then The type of research used in this writing is normative juridical legal research. Legal research is a process of discovering legal rules, legal principles and legal doctrines in order to answer the legal issues faced. This research uses a normative juridical research method, the nature of the research used is descriptive research, the problem approach used in the research is a statutory approach (statute opproach). Conceptual approach and case approach. The results of this research are expected to provide benefits both theoretically and practically. The results of this research are that violations committed by the Chinese government against the Uyghur community include violations of religious freedom, arbitrary detention, mass torture and ill-treatment, as well as increasingly widespread control over daily life. And human rights violations that occurred in China after the enactment of the ICC. This is for the UN Security Council to exercise its powers in adjudicating human rights violations in China.